Risk Mitigation Strategy in Islamic Crowdfunding Institution (Case Study at Islamic Crowdfunding Instituion in Indonesia) - Nabila Zatadini; Nawa Marjany; Syamsuri Syamsuri (AIBPM Publisher, 2019)
Fintech began to grow rapidly in Indonesia, there were 216 institutions that joined the Indonesian fintech organization. One of the fast growing finteches is lending based crowdfunding or P2P lending. At present 127 registered lending based crowdfunding institutions are registered. Unfortunately, crowdfunding growth is still not maximized, found crowdfunding that collapsed in Indonesia, one of which is indves. To avoid failure, a discussion about risk and risk mitigation from crowdfunding is needed. The purpose of this study is to explain the risks arising from various crowdfunding institutions in Indonesia, along with their mitigation strategies. The results of this study are the risk mitigation strategies carried out by crowdfunding institutions in Indonesia by providing super lenders and raising funds again. Suggested implication from this paper is the application of risk mitigation strategy by other crowd funding.